Assessment of the relationship between novel proteins and cardiac cachexia in heart failure patients with reduced ejection fraction: adropin and irisin - Kalkan, A. K.; Cakmak, H. A.; Erturk, M.; Kalkan, K. Erol; Uzun, F.; Tasbulak, O.; Celik, A. (Oxford Univ Press, 2017)
[Abstract Not Available]
Congress of the European-Society-of-Cardiology (ESC) -- AUG 26-30, 2017 -- Barcelona, SPAIN